Abondance et diversité des rotifères dans les mares de thermokarst subartiques - Bégin, Paschale Noël (Université Laval, 2015)
Thermokarst ponds, which are the result of permafrost thawing and erosion, occur in high abundance throughout the North. These ecosystems play a key role as greenhouse gases emitters due to their intense biogeochemical activity. These ecosystems contain a high abundance of rotifers, but little is known about the diversity and ecological role of these microzooplankton in thermokarst waters. In the present study, sampling was conducted in subarctic thermokarst ponds (Nunavik, Canada), and compared with nearby rock-based lakes. The analyses revealed a total of 24 rotifer species. The abundance of rotifers was higher in thermokarst waters than in the rock-based lakes, while diversity was not significantly different. Grazing experiments gave estimates of total community clearance rates of < 0.05% of the water column per day, implying that picoplankton growth rates would readily keep pace with this grazing pressure, and that rotifer populations are unlikely to be bottom-up limited by food availability. Les mares de thermokarst, issues de la fonte du pergélisol, sont très abondantes dans le Nord et émettent des gaz à effet de serre par leur activité biogéochimique intense. Elles contiennent d’abondantes communautés de rotifères dont la diversité et le rôle écologique sont méconnus. Cette étude présente les résultats d’un échantillonnage réalisé dans les mares de thermokarst subarctiques en comparaison avec des plans d’eau sur des bassins rocheux avoisinants. Les analyses ont révélé la présence d’un total de 24 espèces de rotifères. Les rotifères étaient plus abondants dans les mares de thermokarst que dans les bassins rocheux, alors que la diversité n’y était pas différente. Les taux de filtration estimés par des expériences de broutage étaient de moins de 0.05% de la colonne d’eau par jour à l’échelle de la communauté, ce qui implique que les rotifères n’étaient pas limités par la disponibilité de la nourriture dans ces mares.